2014
DOI: 10.5606/archrheumatol.2014.3712
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Bifid Median Nerve and Carpal Tunnel Syndrome: Is it Really a Risk Factor?

Abstract: Objectives: This study aims to determine the bifid median nerve (BMN) frequency in patients with carpal tunnel syndrome (CTS) and to investigate the possible association between CTS and BMN in this patient population. Patients and methods: A total of 194 wrists of 131 patients in whom CTS was diagnosed clinically and electrophysiologically and 73 healthy volunteers without any symptom or sign of CTS were examined with ultrasonography. Results: Bifid median nerve was detected in 22 wrists (11.3%) in CTS group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The second screening was conducted as the full‐text manuscript was sorted. In total, 29 studies were included (Lanz, 1977; Tountas et al, 1987; Amadio, 1988; Iannicelli et al, 2000; Propeck et al, 2000; Gassner et al, 2002; Lindley & Kleinert, 2003; Bayrak et al, 2008; Szopinski & Mazurczak‐Pluta, 2009; Pierre‐Jerome et al, 2010; Granata et al, 2011; Klauser et al, 2011; Mhoon et al, 2012; Walker et al, 2013; Agarwal et al, 2014; Beary et al, 2014; Duymuş et al, 2014; Kasius et al, 2014; Sripathi, Sripathi et al, 2016; Billakota & Hobson‐Webb, 2017; Cartwright et al, 2017; Chen et al, 2017; Kalathummarath, 2017; Petrover et al, 2017; Trachani et al, 2018; Shinagawa et al, 2019; Haris et al, 2021; Park et al, 2021; Dag et al, 2022). These studies were divided into two groups: (a) seven cross‐sectional studies with matching normal or healthy controls, in which the pooled odds ratio and mean difference in CSA were computed (five studies); and (b) 24 cross‐sectional studies without matching control or CTS subjects, in which only the pooled prevalence was computed. The pooled odds ratio of BMN between CTS and normal or control population: 248 BMNs were reported from 2186 CTS wrists, and 100 were reported from 1311 normal (control) wrists.…”
Section: Resultsmentioning
confidence: 99%
“…The second screening was conducted as the full‐text manuscript was sorted. In total, 29 studies were included (Lanz, 1977; Tountas et al, 1987; Amadio, 1988; Iannicelli et al, 2000; Propeck et al, 2000; Gassner et al, 2002; Lindley & Kleinert, 2003; Bayrak et al, 2008; Szopinski & Mazurczak‐Pluta, 2009; Pierre‐Jerome et al, 2010; Granata et al, 2011; Klauser et al, 2011; Mhoon et al, 2012; Walker et al, 2013; Agarwal et al, 2014; Beary et al, 2014; Duymuş et al, 2014; Kasius et al, 2014; Sripathi, Sripathi et al, 2016; Billakota & Hobson‐Webb, 2017; Cartwright et al, 2017; Chen et al, 2017; Kalathummarath, 2017; Petrover et al, 2017; Trachani et al, 2018; Shinagawa et al, 2019; Haris et al, 2021; Park et al, 2021; Dag et al, 2022). These studies were divided into two groups: (a) seven cross‐sectional studies with matching normal or healthy controls, in which the pooled odds ratio and mean difference in CSA were computed (five studies); and (b) 24 cross‐sectional studies without matching control or CTS subjects, in which only the pooled prevalence was computed. The pooled odds ratio of BMN between CTS and normal or control population: 248 BMNs were reported from 2186 CTS wrists, and 100 were reported from 1311 normal (control) wrists.…”
Section: Resultsmentioning
confidence: 99%
“…Another US study showed a similar prevalence between CTS patients and healthy controls and concluded that the bifid median nerve might not be a predisposing factor for CTS. 19 Prior studies reported that the presence of a bifid median nerve might be a risk factor for CTS surgical failure. Jones reported a case of failed bilateral carpal tunnel release as a result of bilateral anomalous palmaris profundus tendons and a bifid median nerve proximal to the flexor retinaculum.…”
Section: Discussionmentioning
confidence: 99%